Radiographic evaluation of narrow-diameter implants from different systems for two years - Fan, Xudong; Cheng, Xiaoya; Wang, Yuanyuan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundNarrow-diameter implants (NDIs) offer a viable alternative to bone augmentation in sites with limited alveolar ridge width. This study aimed to retrospectively evaluate the radiographic marginal bone loss (MBL) and survival rate of NDIs from three different systems after 2 years of functional loading.MethodsIn this retrospective study, a total of 109 NDIs from three brands (30 Straumann®, 38 Thommen, and 41 Osstem) in 78 patients were evaluated. Patient records from 2013 to 2023 were screened. Mesial and distal MBL were measured on periapical radiographs at implant loading and at 3, 6, 12, and 24-month follow-ups. MBL was compared based on implant system, gender, and implant location (anterior/posterior, maxilla/mandible).ResultsThe overall 2-year implant survival rate was 98.17%. Two implants failed within the first 6 months. The mean MBL at 24 months was 1.67 ± 0.66 mm. Straumann® implants (made of TiZr alloy) showed significantly less MBL than Osstem implants (made of Grade IV titanium) at multiple time points (P < 0.05). Female patients exhibited significantly higher mesial MBL than male patients at 6 and 12 months (P < 0.05). Implants in the posterior region showed greater mesial MBL than those in the anterior region at 3 months (P < 0.05).ConclusionWithin the limitations of this study, NDIs demonstrated a high 2-year survival rate, supporting their use in anatomically restricted sites. The implant system, particularly the material and design, significantly influenced MBL. The TiZr alloy implant system was associated with the least bone loss. Patient- and site-specific factors, such as gender and posterior location, were also associated with greater MBL in the early healing phase, highlighting the multifactorial nature of peri-implant bone preservation.